Biological performance of different Chilo partellus populations on diverse maize genotypes - SAMAL, IPSITA; DHILLON, MUKESH K; TANWAR, ADITYA K; BHOI, TANMAYA K (The Indian Journal of Agricultural Sciences, 2021)
Genetic variation within plants and herbivores influence the biological attributes and insect-plant interactions. We studied biological performance of different agro-ecological Chilo partellus (Swinhoe) populations on diverse maize genotypes during 2016-17 at ICAR-Indian Agricultural Research Institute, New Delhi. There was significant variation in larval period, larval survival, pupal period, pupal weight, and adult emergence of C. partellus populations on the test maize genotypes. Larval period of Hisar, and pupal periods of Hisar and Parbhani populations were significantly longer than other C. partellus populations across test maize genotypes. Pupal weight across maize genotypes was significantly higher in Delhi as compared to other populations. Larval survival and adult emergence were significantly higher in Delhi and Hisar, while lower in Raichur and Parbhani populations than other C. partellus populations across maize genotypes. Longer developmental periods, lower survival and adult emergence of C. partellus across populations on CPM 2 and CPM 8 indicate stable resistance in these maize genotypes against this pest. Higher survival in Hisar and Delhi populations across maize genotypes indicate their higher aggressiveness than other C. partellus populations. The differential resistance reaction, development and survival of different stem borer populations on diverse maize genotypes indicate the existence of different biotypes/ecotypes of C. partellus in India.